INFORMATION MANAGEMENT AND HUMAN RESOURCE MANAGEMENT PRACTICES AMONG PRINCIPALS IN SECONDARY SCHOOLS IN IMO STATE - C. Ndu, Afam (African Journal of Social and Behavioural Sciences, 2024)
This research was carried out to determine principals’ information management and human resource management practices in secondary schools in Imo State. It sought to determine if there is a relationship between principals’ information management and their orientation of new teachers, staff development, motivation and discipline of teachers. The study drew heavily from the resource dependency theory, organizational information processing theory and organizational information theory. It employed a correlational research design. Four research questions guided the study. The four hypotheses developed for the study were tested at a 0.05 level of significance. A proportionate stratified random sampling technique was used to select 113 schools, which is 40 percent of the 279 schools in Imo State. Again, 40 per cent of teachers in the 113 schools were selected using a stratified sampling technique. Data was collected by means of a 68-item questionnaire consisting of two sections, one on information management and the other on human resource management. The section on human resource management was organized into four categories, namely staff orientation, staff development, staff motivation, and staff discipline, in order to highlight essential human resource management practices undertaken by secondary school principals. Only teachers were used as respondents. The instrument's reliability was assessed using the Cronbach Alpha Coefficient, which yielded a reliability index, while the Pearson Moment Correlation Coefficient was employed for data analysis. The study observed a highly positive relationship between principals’ information management and all four categories of human resource management studied. Based on the findings of the study, it was recommended that schools should, among other things, upgrade their information resources and facilities like libraries, databases and internet connectivity.